Water column raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO294 - Michael Riedel; Ingo Klaucke; Karen Louise Douglas; Jessie Kehew; Mia Schumacher (PANGAEA, 2024)
Raw water column data were collected aboard RV SONNE during cruise SO294 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 13.09. 2022 – 27.10. 2022 from Vancouver (Canada) – Port Hueneme (USA) in the central Pacific Ocean. The main objective of SO294 was designated towards the project CLOCKS: "Northern Cascadia: Extent of locked zone, prism deformation, slip-to-toe, and the edge of subduction". A secondary user project was added to SO294 to utilise the opportunity provided by the vessel operating off the West Coast of Canada. This project is a collaborative study between GEOMAR and Ocean Networks Canada (ONC) on potential CO2 storage in marine basalt complexes called CASCADIA CO2 (CCO2). Data were recorded within the Canadian EEZ. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.